Textualizing Kinaray-a in the Republic of letters - Talledo, Tomasito T. (Danyag :the UPV journal of humanities and social sciences, 2009)
"This paper critiques nostalgia as traditional element in Kinaray-a poetry but instead submits for optimistic outlook for creative writers. This submission is exemplified in the excerpts of the author's long poetic works, plays and discourses with fellow contemporary Kinaray-a writers. The author's works are self-reviewed to forward the proper recognition of Kinaray-a's status as language of creative writing or its textualization. Several suggestions for creative writers in Kinaray-a are made in relation to their expected task of textualization."